Financial competencies as investigated in the nursing field: Findings of a scoping review. (30th May 2022) - Bayram, Aysun; Pokorná, Andrea; Ličen, Sabina; Beharková, Natália; Saibertová, Simona; Wilhelmová, Radka; Prosen, Mirko; Karnjus, Igor; Buchtová, Barbora; Palese, Alvisa
Abstract: Aim(s): This study aims to map the extent of the research activity in the field of financial competencies and nursing and identify main patterns, advances, gaps, and evidence produced to date. Background: Financial competencies are important indicators of professionalism and may influence the quality of care in nursing; moreover, these competencies are the basis of health care sustainability. Despite their relevance, studies available on financial competencies in the nursing field have not been mapped to date. Evaluation: A scoping review was guided according to (a) the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for Scoping Review and (b) the Patterns, Advances, Gaps and Evidence for practice and Research recommendations framework. Key issue(s): A total of 21 studies were included. Main research patterns have been developing/evaluating the effectiveness of education programmes and investigating the nurse's role in the context of financial management, challenges and needs perceived by them, and tool validation to assess these competencies. The most frequently used concept across studies was 'financial management competencies' ( n = 19). Conclusion(s): The sparse production of studies across countries suggests that there is a need to invest in this research field. Implications for nursing management: Nurses with managerial roles should invest in their financial competencies by requiring formal training both at the academic and at the continuing education levels. They should also promote educational initiatives for clinical nurses, to increase their capacity to contribute, understand, and manage the emerging financial issues.